2005
DOI: 10.1073/pnas.0500491102
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation without parameter change: Dynamic gain control in motion detection

Abstract: Many sensory systems adapt their input-output relationship to changes in the statistics of the ambient stimulus. Such adaptive behavior has been measured in a motion detection sensitive neuron of the fly visual system, H1. The rapid adaptation of the velocity response gain has been interpreted as evidence of optimal matching of the H1 response to the dynamic range of the stimulus, thereby maximizing its information transmission. Here, we show that correlation-type motion detectors, which are commonly thought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 18 publications
(17 reference statements)
9
142
0
2
Order By: Relevance
“…Another (or additional) possibility is that stimulus-dependent changes in STRFs may arise not from changes in RF parameters but instead from a stationary nonlinearity in the response function (e.g., as suggested by Theunissen et al, 2000;Escabí and Schreiner, 2002;Valentine and Eggermont, 2004). [A similar point has been raised recently in studies of adaptation of motion detection in the fly visual system (Borst et al, 2005).] Adaptation is ubiquitous in the brain and surely plays an important role in Figure 9.…”
Section: Discussionmentioning
confidence: 92%
“…Another (or additional) possibility is that stimulus-dependent changes in STRFs may arise not from changes in RF parameters but instead from a stationary nonlinearity in the response function (e.g., as suggested by Theunissen et al, 2000;Escabí and Schreiner, 2002;Valentine and Eggermont, 2004). [A similar point has been raised recently in studies of adaptation of motion detection in the fly visual system (Borst et al, 2005).] Adaptation is ubiquitous in the brain and surely plays an important role in Figure 9.…”
Section: Discussionmentioning
confidence: 92%
“…A fast alignment of the input-output gain of TCs with the SD of velocity fluctuations can be attributed to inherent properties of correlationbased motion detectors, which are thought to form the computational principle of fly motion detection (Borst et al, 2005). Because these inherent processes evolve very fast after a change in stimulus parameters, they will probably not contribute much to the rather slow adaptation phenomena observed with our stimulation paradigm (Figs.…”
Section: Mechanisms Underlying the Observed Changes In Response Propementioning
confidence: 99%
“…Although several changes in response properties of fly TCs with ongoing visual motion stimulation have been described (Maddess and Laughlin, 1985;Brenner et al, 2000;Harris et al, 2000;Borst et al, 2005), comparatively little is known about the underlying cellular mechanisms of motion adaptation. A fast alignment of the input-output gain of TCs with the SD of velocity fluctuations can be attributed to inherent properties of correlationbased motion detectors, which are thought to form the computational principle of fly motion detection (Borst et al, 2005).…”
Section: Mechanisms Underlying the Observed Changes In Response Propementioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, it has been shown that even more complex changes in response proper es are emergent proper es of the EMD. In par cular, both in recordings from TCs as well as in EMD models with fi xed parameters, it was observed that the slope of the neuronal input-output funcon changes when random velocity fl uctuaons of diff erent modula on depths are presented (Borst et al 2005). This phenomenon was termed "adapta on without parameter change" to diff eren ate it from "adapta on" in a strict sense, for which genuine changes in system parameters have to be present.…”
Section: The Computa Onal Principle Of Visual Mo On Detec On and Its mentioning
confidence: 99%